IMPLEMENTASI PROGRAM TAHASSUS DALAM MENINGKATKAN KUALITAS LULUSAN DI MAN 2 DARUL ULUM JOMBANG - Fadlilah, Ainul (Al Tadib : Jurnal Ilmu Pendidikan, 2023)
This article discusses the implementation of the takhassus program of the Koran and the yellow book. Through the Tahassus program, it is expected to improve the quality of graduates. The focus of this research is how to implement the tahassus program in improving the quality of student graduates and what are the supporting and inhibiting factors in implementing the tahassus program at MAN 2 Darul Ulum Peterongan Jombang. Using a case study with data collection techniques of observation, interviews, and documentation as well as data analysis in the form of qualitative descriptive. The results showed that there were several stages in the implementation or implementation of the tahassus program at MAN 2 Peterongan Jombang, namely the planning, implementation and evaluation stages. The method used in carrying out takhassus is the tahfidz and takrir methods. Special tests or exams are carried out once a month and in each semester. After the tahssus exam process is complete, students who do not pass the exam will be allowed to take part in remedial to improve the tahssus exam scores. Factors that support the implementation of the tahassus program are the support of teachers and parents and the implementation of the tahssus program is carried out in a religious educational environment (a pesantren environment). While the inhibiting factor is that students feel lazy, the physical condition of students is not healthy, students are often sleepy, and students are less focused on carrying out special interest learning.